(3GdeQLY aj GdJacjQ GdGSJQGJjLj hGdGOGQI GdGSJQGJjLjIs - (3eUWaj eMehO(B, (3CHh HcQs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3GdGWGQ GdYGe ddGOGQI GdGSJQGJjLjI hfXGe GdJNWjW GdGSJQGJjLj, GdJacjQ GdGSJQGJjLj hGdGOGQI GdGSJQGJjLjI, OQGSI GdHjFI GdOGNdjI ddefXeI heeGQSI GdGOGQI ddGSJQGJjLjI, OQGSI hJMdjd GdHjFI GdNGQLjI, eeGQSI GdGOGQI GdGSJQGJjLjI, QSGdI GdefXeI, GdCgOGa GdGSJQGJjLjI, GdaQVjGJ GdGSJQGJjLjI, GdGSJQGJjLjGJ, GSJQGJjLjGJ GdhXGFa (B((3GdHOGFd GdGSJQGJjLjI Ydi eSJhi GdhXGFa(B)(3, eQGLYI GdGSJQGJjLjGJ hJfajPgG(B.s
Keywords: (3EOGQI GdCYeGds; (3GdESJQGJjLjIs; (3GdJNWjWs